Applying for Social Housing in Australia – The Centrality of Cultural, Social and Emotional Capital. Issue 1 (1st January 2023) - Morris, Alan; Clarke, Andrew; Robinson, Catherine; Idle, Jan; Parsell, Cameron
ABSTRACT: Social housing scarcity has underpinned the development of detailed social housing application processes across Australia. Applications require the strongest possible evidence of disadvantage and need, conceptualized in this paper as the required demonstration of "inverse distinction". Drawing on 47 in-depth interviews in three Australian states with people who have expert knowledge of the application process, we argue that the onerous requirements of the application means that if an applicant does not have a skilled supporter or advocate, they are less likely to achieve an optimal result. Drawing on Bourdieu's framework and the concept of emotional capital, we demonstrate that being prioritized invariably involves an applicant sub-contracting cultural and social capital to an advocate. Further, the latter needs to have the requisite emotional capital. This article shines new light on the practical and emotional workload of social housing applications for both housing professionals and those in need of housing assistance.